Management of Jejunoileal Atresia : Our 5 year Experience (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Purpose: The purpose of the study was to see the outcome of primary anastomosis and enterostomy in jejunoileal atresia, to identify the complications associated with these surgical procedures and to find out a preferable surgical option for the complicated atresia. Methods: This prospective study was carried out in the Department of pediatric Surgery, in a tertiary pediatric hospital during the period of 5 years (July 2006 to June 2011). The study included neonates of both sexes, who were per operatively diagnosed as jejuno-ileal atresia. We excluded the patients of jejunoileal atersia with associated major anomaly like complex ARM, gastroschisis, omphalocele etc. Results: During this study period, a total 176 patients were diagnosed as jejunoileal atresia. Twelve of them were excluded due to presence of major associated anomaly. So the sample size was 164. Resection and primary anastomosis were done in 132 jejunoileal atresia with or without gangrene. Enterostomy were done in 32 cases, complicated by perforation of proximal segment with gangrene and peritoneal soiling. Mortality was higher after primary anastomosis in complicated atresia but much better than enterostomy. Complications were also more frequent and troublesome after enterostomy. Conclusion: Primary anastomosis gave better outcome in all types of jejuno-ileal atresia with or without complication which reduce the post operative morbidity and mortality. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 52-55